Pearling Instabilities of a Viscoelastic Thread - Deblais, A; Velikov, K P; Bonn, D (Physical review letters, 2018)
Pearling instabilities of slender viscoelastic threads have received much attention, but remain incompletely understood. We study the instabilities in polymer solutions subject to uniaxial elongational flow. Two distinctly different instabilites are observed: beads on a string and blistering. The beads-on-a-string structure arises from a capillary instability whereas the blistering instability has a different origin: it is due to a coupling between stress and polymer concentration. By varying the temperature to change the solution properties we elucidate the interplay between flow and phase separation.